Clima organizacional y desempeño laboral del personal administrativo de la Policía Nacional de Loja, año 2022 - Jaramillo Peña, Nathaly Briggette (2023)
Currently, the organizational climate has become a fundamental issue within the institutions, since having a good organizational climate will be reflected in a good job performance of its employees and as a result, the institutional objectives will be achieved; Therefore, the present investigation was developed with the purpose of establishing the relationship of the organizational climate with the work performance of the administrative servers of the Loja National Police, year 2022, starting from its diagnosis and identifying the factors of the organizational climate that are related with work performance, which allowed to propose different proposals for the improvement of the institution. Adding to the above, a non-experimental descriptive and explanatory investigation was carried out. The population under study was 48 administrative servers, for which the instruments such as the survey and the interview were applied. The methods and instruments applied made it possible to achieve the objectives set and reach the conclusion that it was possible to establish the relationship between the organizational climate and the work performance of the administrative servers of the Loja National Police, year 2022, through the surveys, and interviews carried out, as well as using the Chi-square method where with a P-value equal to 1.4052E-11 statistical evidence was found to reject the null hypothesis (Ho), and accept the alternative hypothesis (Ha), therefore both "The organizational climate is related to the work performance of the administrative servers who work in the Loja National Police". And finally with the elaboration of the proposal for the improvement of work performance. In the institution it was determined that in the relationship factor, there are divided criteria since a part of the staff consider that there is an atmosphere of friendship, as well as some believe the opposite. Likewise, in the study of job performance factors, it can be seen that the most favorable factors within the institution are motivation and communication, since having motivated servers will perform much better because they feel better in their position and will do it. more effectively, as well as increase their commitment.